Profile Orientation and Social Distance in Portrait Painting. (November 2013) - Coles, P R
A study of portrait paintings by various artists revealed that the sitter's face is more likely to be illuminated by a light source to the artist's left than to his right. Although the sitter's face may be turned towards the artist's left or right side with equal frequency, the interaction of illumination and profile orientation does not appear to be arbitrary. This finding is interpreted in the context of other findings on left and right in picture perception, and a new explanation of the relationship between profile orientation and the personality of the sitter is offered.